Routine Administration of a Multispecies Probiotic Containing Bifidobacterium and Lactobacillus to Very Low Birth Weight Infants Had No Significant Impact on the Incidence of Necrotizing Enterocolitis - Juber, Brian A.; Boly, Timothy J.; Pitcher, Graeme J.; McElroy, Steven J. (Frontiers in Pediatrics, 2021)
Necrotizing enterocolitis (NEC) is the leading cause of gastrointestinal morbidity in preterm infants, and prevention and treatment strategies have remained largely unchanged over the past several decades. As understanding of the microbiome has increased, probiotics have been hypothesized as a possible strategy for decreasing rates of NEC. However, a recent AAP report cited caution on the use of probiotic use in part because studies of probiotic use in ELBW infants are lacking. As our unit began routine probiotic use in 2015 and we are a leading institution for intact survival of ELBW infants, we attempted to answer if probiotic use can impact NEC incidence in VLBW and ELBW infants. We conducted a single-center retrospective chart review of infants with modified Bell’s stage ≥2a NEC for the 4 years prior to and 5 years after initiation of a protocol involving routine supplementation of a multispecies probiotic to premature infants. The primary outcome measures were NEC and all-cause pre-discharge mortality. In our institution, neither the rates of modified Bell’s stage ≥2a NEC, nor the rates of all-cause mortality were significantly altered in very low birth weight (VLBW) infants by the initiation of routine probiotic use (NEC rates pre-probiotic 2.1% versus post-probiotic 1.5%; all-cause mortality rates pre-probiotic 8.4% versus post-probiotic 7.4%). Characteristics of our two cohorts were overall similar except for a significantly lower 5-minute APGAR score in infants in the post-probiotic epoch (pre-probiotic 8 versus post-probiotic 6 p=0.0316), and significantly more infants in the post-probiotic epoch received probiotics (pre-probiotics 0% versus post-probiotics 65%; p<0.0001). Similarly, probiotic use had no impact on the incidence of NEC when we restricted our data to only extremely low birth weight (ELBW) infants (pre-probiotics 1.6% vs post-probiotics 4.1%). When we restricted our analysis to only inborn infants, probiotics still had no impact on NEC rates in VLBW infants (1.5% pre- and 1.1% post-probiotic, p=0.61) or ELBW infants (2% pre- and 2.1% post-probiotic, p=0.99) Contrary to other studies, we found no significant difference in rates of modified Bell’s stage ≥2a NEC or all-cause pre-discharge mortality in VLBW infants following routine administration of a multispecies probiotic supplement.